2021
DOI: 10.9734/ijpr/2021/v8i130193
|View full text |Cite
|
Sign up to set email alerts
|

Chyavanprash: A Multimodal Approach to COVID-19 Management

Abstract: The word Chyavanprash (CP) comprises of ‘Chyawan’ and ‘Prasha’. Chyavan represents ‘degenerative change’ and Prasha symbolises a drug. Enhancement of immunity and longevity of life were the main reasons for which CP was consumed since ancient times. CP has about 50 herbs, spices and minerals along with a range of pharmacological activities on almost all organ systems of the human body. COVID-19 actually means coronavirus disease 2019. COVID-19 targets and affects multiple organs like lungs, heart, kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A recent scoping review concluded that preclinical studies show promising results for the use of MAK as an anticancer and chemoprotective agent ( 25 ). Furthermore, the results of Zanella et al ( 19 ), who placed healthy individuals on a diet with or without MAK, showed that a MAK-enriched diet decreased oxidative stress parameters and increased antioxidant defenses in both short- and long-term treatments ( 12 ). Research into the phytochemical aspects of the plants that form the basis for the production of MAK has also shown promising prospects for the treatment of oxidative stress and cancer ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent scoping review concluded that preclinical studies show promising results for the use of MAK as an anticancer and chemoprotective agent ( 25 ). Furthermore, the results of Zanella et al ( 19 ), who placed healthy individuals on a diet with or without MAK, showed that a MAK-enriched diet decreased oxidative stress parameters and increased antioxidant defenses in both short- and long-term treatments ( 12 ). Research into the phytochemical aspects of the plants that form the basis for the production of MAK has also shown promising prospects for the treatment of oxidative stress and cancer ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MAK preparation is complex, with a range of pharmacological activities on various organ systems. In terms of its preparation, it is comparable to the classic Ayurvedic formulation Chyavanprash with regard to numerous ingredients (e.g., Emblica officinalis ) for which mechanisms have been discussed ( 11 , 12 ). Studies have shown that Chyavanprash has immunostimulatory effects, enhancing the secretion of cytokines and stimulating macrophage and natural killer cell activity ( 13 ).…”
Section: Introductionmentioning
confidence: 99%